PELAKSANAAN SUPERVISI AKADEMIK OLEH KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SD NEGERI 52 BANDA ACEH - Nur Maneh; Cut Zahri Harun; Bahrun . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Academic supervision aims at influencing and developing the behavior of the teacher in managing the learning process at school. The purpose of this study was to find out: the implementation of academic supervision for the completeness of teacher administration, discipline of teachers, the commitment of teachers, and the obstacles to the implementation of academic supervision to manage the learning process. Method with a qualitative approach, data collection techniques used were observation, interview, and documentation studies. Subjects of the study were principal and teachers. The results of the research showed that: (1) the implementation of academic supervision for the completeness of teacher administration has been carried out well by the principal. The principal as the supervisor always tried to guide and direct the teachers, mainly in completing learning tools such as annual program, semester program, syllabus, and lesson plan; (2) the implementation of academic supervision to enhance the discipline of teachers has been carried out well by the principal; (3) the implementation of academic supervision to improve the commitment of teachers have been applied well by the principal; and (4) the obstacles to the implementation of academic supervision in the management of the learning process was lack of time of principal because of other tasks. The academic supervision was conducted by the vice principal and senior teachers, but the improvement and guidance were not well implanted.Keywords: academic supervision, principal, and teacher performance